Maternal knowledge and family support as predictors of Posyandu attendance among under-five children - Azim, La Ode Liaumin (Arsip Keilmuan Gizi (AKG), 2026)
Visits by toddlers to Posyandu (integrated health service posts) are an important indicator in monitoring child health in Indonesia. Visits by toddlers to Posyandu in Muna District are still very low, at 41.6% in 2024. Maternal knowledge and family support play a role in encouraging toddlers’ participation in Posyandu activities. This study aimed to analyze the relationship between maternal knowledge and family support on the frequency of toddlers’ visits to Posyandu in Masalili Village, Muna District. This study used a quantitative design with a cross-sectional approach. The research sample consisted of 57 families with toddlers selected randomly from Masalili Village. Data were collected through questionnaires that measured the level of maternal knowledge, family support, and the frequency of toddler visits to Posyandu. Data analysis was performed using the chi-square statistical test using the SPSS application. The results showed that there was a relationship between knowledge and toddlers’ attendance to the Posyandu (p=0.001) and that there was a relationship between family support and toddlers’ attendance to the Posyandu (p=0.024). Maternal knowledge and family support play an important role in increasing the frequency of toddlers’ attendance to the Posyandu. Therefore, efforts to increase maternal knowledge and strengthen family support should be the main focus of public health programs in the area.